The effects of workforce diversity towards the employee performance in an organization. - Chew, Eugene WeiLiang; Lee, Kah Mun; Tan, Siew Chern; Tee, Say Fong (2011)
Diversity is increasingly recognized and utilized as an important organizational resource in regards to whether the goal is to be an employer of choice, to provide excellent customer service, or to maintain a competitive edge. Workplace diversity is a multi-faceted concept that will continue to evolve as more industries move toward a global marketplace. It also has proven to have led to a perception of being fundamental for employee performance. This fundamental belief forces managers to embrace and comprehend the concept of workplace diversity, its barriers and benefits. The purpose of this research is to investigate the effect of work force diversify towards employee performance in an organization which focus into air line industry. The research also focuses on workforce diversity which includes the gender, age, ethnic and education background of the employees which is the most critical variables among all the others. The investigation was done by distributing 300 questionnaire to the air line industry„s management team. The questionnaire results show that there is a significant impact on performance when different workforce is working in the airline industry.